RELATION BETWEEN FEEDING PRACTICES AND DISEASE INCIDENCE IN DAIRY ANIMALS OF PUNJAB - KRISHANDEV,; VERMA, HK; KASRIJA, R; SINGH, J (The Indian Journal of Animal Reproduction, 2016)
Dairy farmers (30 from each of the six different agro-climatic zones of Punjab state) rearing >5 dairy animals each were randomly selected and interviewed. In different zones of Punjab, there was variation (p
Keywords: Anestrus; Dairy; Feeding; Punjab; Repeat breeding